Rancangan Awal Model Pembelajaran Atletik Berbasis Permainan Tradisional untuk Sekolah Dasar - Amlin Amlin; Hariadi Said; Mirdayani Pauweni (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study is to produce an initial design of an athletics learning model based on traditional games. The method used is descriptive analysis as a preliminary study within a series of research and development activities. The results of the study are in the form of an initial design of an athletics learning model based on the traditional game boy-boyan, which will be validated by experts and revised based on their feedback. In conclusion, the final model will be obtained after a series of trials and revisions.   Keywords: Athletics Learning, Learning Model, Primary School Students, Traditional Games